REFLEKSI HIBRIDITAS BUDAYA DALAM PANCASILA PADA REALITAS DAN MEDIA SEBAGAI IDENTITAS BANGSA - Rustono Farady Marta (Universitas Bunda Mulia, 2017)
Studies on the identity are being learned widely, mostly focus on specific groups. The reality we face today is shows the different conditions, because Indonesia has Pancasila as the state philosophy that clearly asserts the motto of